2020
DOI: 10.3847/1538-3881/ab5b11
|View full text |Cite
|
Sign up to set email alerts
|

Population-level Eccentricity Distributions of Imaged Exoplanets and Brown Dwarf Companions: Dynamical Evidence for Distinct Formation Channels*

Abstract: The orbital eccentricities of directly imaged exoplanets and brown dwarf companions provide clues about their formation and dynamical histories. We combine new high-contrast imaging observations of substellar companions obtained primarily with Keck/NIRC2 together with astrometry from the literature to test for differences in the population-level eccentricity distributions of 27 long-period giant planets and brown dwarf companions between 5-100 AU using hierarchical Bayesian modeling. Orbit fits are performed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
170
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(192 citation statements)
references
References 234 publications
(205 reference statements)
20
170
2
Order By: Relevance
“…HD33632Ab's eccentricity posterior probability distribution has a 68% upper limit of 0.29. This is smaller than the eccentricities of most brown dwarfs studied in Bowler et al (2020), who argue that systematically higher eccentricities of brown dwarf-mass companions relative to exoplanets point to a The orbit fits used Hipparcos and Gaia absolute astrometry, Lick Observatory precision radial-velocity measurements for HD 33632 Aa, and relative astrometry of HD 33632 Ab. The posterior on HD 33632 Aa's mass is dominated by our adopted prior of 1.1±0.1M e .…”
Section: Discussionmentioning
confidence: 96%
“…HD33632Ab's eccentricity posterior probability distribution has a 68% upper limit of 0.29. This is smaller than the eccentricities of most brown dwarfs studied in Bowler et al (2020), who argue that systematically higher eccentricities of brown dwarf-mass companions relative to exoplanets point to a The orbit fits used Hipparcos and Gaia absolute astrometry, Lick Observatory precision radial-velocity measurements for HD 33632 Aa, and relative astrometry of HD 33632 Ab. The posterior on HD 33632 Aa's mass is dominated by our adopted prior of 1.1±0.1M e .…”
Section: Discussionmentioning
confidence: 96%
“…For the eccentricity distribution, we considered the recent results derived by Bowler et al (2020) for directly imaged exoplanets and brown dwarf companions. For this parameter we adopted a Beta distribution with parameters [α = 0.95, β = 1.30], which corresponds to the best fit to the full sample of wide substellar companions studied in Bowler et al (2020). For each simulated companion, we then computed the corresponding projected separation from the drawn orbital elements and the semimajor axis a of that grid point.…”
Section: Survey Sensitivitymentioning
confidence: 99%
“…Both the stellar obliquity and orbital eccentricity are clues about the formation and subsequent dynamical history of planetary systems. For example, based on direct imaging data, Bowler et al (2020) reported a difference in the eccentricity distributions of planets and brown dwarfs, evidence that these objects form in different ways. Planets are expected to form on circular and coplanar orbits within protoplanetary disks, although they can develop nonzero eccentricities via planet/ planet interactions (Rasio & Ford 1996), secular von Zeipel-Lidov-Kozai cycles (Naoz 2016;Ito & Ohtsuka 2019), planetdisk interactions (Goldreich & Sari 2003), or other dynamical processes.…”
Section: Introductionmentioning
confidence: 99%